Perilaku Sunda Sebagai Entitas Karakter Kebangsaan yang Terancam Hilang - Parhan, Muhamad (Studi Budaya Nusantara, 2021)
The phenomenon of ethical and moral degradation has become a discussion and complaint of every society. The values of politeness which are the core of a human being who are marginalized by the hegemony of science and technology development. There is nothing wrong with the development of science and technology, but society seems not yet ready to accept the onslaught of the new and talkative cultures that adopt them. This study wanted to determine the level of application of Sundanese values in everyday community interactions. In addition, it measures people's concern in transferring Sundanese values to the younger generation. The research method used is descriptive qualitative. The data were obtained using a google form filled out by 117 respondents. The data were filled in by respondents aged 19-21 years, the rest were respondents aged 25-50 years. The data shows that respondents who strongly apply Sundanese values in their daily life and do not feel proud. The data also shows that of the people who take part in transferring these local wisdom values, the minimum is the value of technical courtesy that is carried out in the need of interaction. For example, in speaking kind words to older people, getting in love, and saying excuse me when in society. This is if teachers and familiarize themselves at every level of society, it will form a harmonious national character. National character is the main asset and value if it is owned by individuals. Having this will attract him to other people and become a unique identity. There are still people who care about the preservation of local wisdom values, only transferred in different ways. This is because the character of society has also shifted due to various times of development.